A theoretical framework for the concept of ‘Internet strategy' - Benita Steyn; Anské Grobler; Berdine Cilliers (Communicare)
Organisations know that the Internet could or should play an important role in goal achievement, but are uncertain about its strategic application. It can therefore be said that the Internet remains largely ‘a technology in search of a strategy’. This article explores ‘Internet strategy’ from the perspective of the corporate communication domain, specifically within the framework of two meta-theoretical approaches: the Excellence approach and the two-way symmetrical approach to public relations and communication management. ‘Internet strategy’ is conceptualised based on the following theories: information theory, the communication process, mass communication theory, strategic management theory, corporate communication roles theory, and the models for developing corporate communication strategy and communication plans. The most important findings indicate that, with regard to the corporate communication process, the Internet is regarded as a medium or channel and, as such, it can make a contribution on all strategy levels. The concept of ‘Internet strategy’ is specifically seen to be part of operational strategy at the micro organisational level. However, considering the use of the Internet already at the functional strategy level ensures that its use is not decided upon in isolation, but forms part of corporate communication goal achievement.